2000
DOI: 10.1295/polymj.32.269
|View full text |Cite
|
Sign up to set email alerts
|

Complex Formation of Silk Fibroin with Poly(acrylic acid)

Abstract: ABSTRACT:Silk fibroin (SF) and poly(acrylic acid) (PAA) can interact when their aqueous solutions were mixed. Viscometric study showed that SF/PAA complex formation depended on the ratios of SF and PAA in dilute solution. SF/ PAA complexes varied from soluble state to gel and to precipitate when both concentrations of mixed solution were increased gradually. FT-IR results showed that PAA and SF were liable to form interpolymer hydrogen bonds, and SF conformation changed in the complexes. FT-IR spectra also sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 46 publications
(6 reference statements)
2
13
0
Order By: Relevance
“…Many properties, such as water absorption and mechanical properties, have been improved by using polymer blending techniques [13][14][15][16][17][18][19][20][21][22].…”
Section: Introduction T Issue Engineering Involves Providing Sufficiementioning
confidence: 99%
“…Many properties, such as water absorption and mechanical properties, have been improved by using polymer blending techniques [13][14][15][16][17][18][19][20][21][22].…”
Section: Introduction T Issue Engineering Involves Providing Sufficiementioning
confidence: 99%
“…While BSA‐loaded chitosan and O ‐HTCC nanoparticles exhibited two relatively broader peaks at 2θ 15 and narrow peaks at 2θ 22. It was well‐known that the width of XRD peak was related to the size of crystallite, the broadened peak usually resulted from small crystallites 38. Hence, in this reaction, the reaction between BSA and chitosan and O ‐HTCC first took place preferentially in the amorphous region and then proceeded very moderately from the edge to the inside of the crystalline region39, 40 and with further reaction between BSA and chitosan or O ‐HTCC, the original crystalline structure of BSA was destroyed and the new crystalline stucture appeared.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the peaks of QCMCO-3, QCMCO-6 and QCMCO-9, it can be found that with higher DS of carboxymethyl groups, the peak became broader. It is well known that the width of X-ray diffraction peak is related to the size of crystallite, the broadened peak usually results from small crystallites (14). Hence, in this reaction, the carboxymethylation reaction first took place preferentially in the amorphous region and then proceeded very moderately from the edge to the inside of the crystalline region (15).…”
Section: Structure Characterization Of Qcmcosmentioning
confidence: 99%